Adding Fast Parity Check to BST for Concurrent Monitoring - J. Santos (1999)
(POSTER)Recent proposals rely on data scanned through BST in several applications, namely to provide on-line decisions inside dependable ICs. This means the need to have confidence in the string entering the target IC. Our proposal is to allow the on-board BST controller to have access to the parity of this data immediately after the scan operation. With a minor enhancement to the TAP controller, in case of error the scan operation can be repeated immediately.